Cortical networks are disturbed in people with cirrhosis even in the absence of neuropsychometric impairment. Issue 3 (March 2019) - Olesen, Søren S.; Jackson, Clive D.; Gram, Mikkel; Zacharias, Harry D.; Dirks, Meike; Weissenborn, Karin; Drewes, Asbjørn M.; Morgan, Marsha Y.
Highlights: Neuronal networks were explored in patients with cirrhosis using advanced EEG computational analysis. Significant disruption of cortical networks was found even in the absence of hepatic encephalopathy. The findings provide new insights into the cortical signature of this syndrome and its pathophysiology. Abstract: Objective: Hepatic encephalopathy is a common complication of cirrhosis; it is characterised by neuropsychometric/neurophysiological abnormalities. Its pathophysiology is complex but glial neuronal communication is likely to be disrupted and to impact on oscillatory networks and cortical connectivity. The aim of this study was to use multichannel electroencephalography (EEG) to investigate functional connectivity, as a surrogate for cortical networks, in patients with cirrhosis. Methods: Resting EEGs were recorded in 98 healthy controls and in 264 patients with cirrhosis characterised psychometrically using the Psychometric Hepatic Encephalopathy Score (PHES). Functional connectivity was calculated using the phase-lag index with stratification into standard EEG frequency bands. The findings were validated in a further cohort of 39 healthy controls and 106 patients with cirrhosis. Results: Widespread disruption in functional connectivity was observed in the patients compared with the controls; connectivity was increased in the theta (4–8 Hz) band and decreased in the delta (1–3.5 Hz), alpha (8.5–13 Hz) and beta (13.5–26.5 Hz) bands. Changes were apparent even in patients who were psychometrically unimpaired compared with healthy controls viz mean ± SEM theta 0.107 ± 0.001 vs . 0.103 ± 0.002 (p < 0.05) and alpha 0.139 ± 0.003 vs. 0.154 ± 0.003 (p < 0.01); more pronounced changes were observed with increasing neuropsychometric impairment. The findings were replicated in the second cohort. Conclusions: Cortical networks are disturbed in patients with cirrhosis even in the absence of psychometric impairment. Significance: These findings will facilitate further exploration of the pathophysiology of this condition and provide a robust means for assessing treatment effects in research settings.